Urea as a therapeutic option in inadequate antidiuresis syndrome - Salas-Rodríguez, Carolina (2023)
Syndrome of Inappropriate Antidiuresis (SIAD), is produced by an alteration in the hypothalamus-neurohypophysis axis due to a failure in the osmotic regulatory response or non-osmotic factors, with complications directly related to the degree of hyponatremia and impact on quality of life and patient mortality. Management consists of normalization of natremia, and the search for the underlying etiology. We present the case of an adult patient diagnosed with idiopathic SIAD and associated neurocognitive disorder, with a favorable response to treatment with urea.